2010
DOI: 10.4028/www.scientific.net/ast.62.169
|View full text |Cite
|
Sign up to set email alerts
|

Saccharides Derivatives in Shaping of Ceramic Powders – New Monomers and Dispersants

Abstract: Saccharides, particularly monosaccharides, as well as their derivatives, were found to be a group of effectively working processing agents in case of alumina which has been used as a solid phase of highly loaded suspensions. The synthesis of new low-toxic monomers obtained from saccharides is reported and their application in gelcasting process is presented. The synthesized monomer named 3-O-acrylic-D-glucose is an interesting alternative for the commercially available acrylic monomers. The present paper descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Hence searching for biodegradable alternatives but still can provide low viscosity to replace traditional ceramic additives has become a focused area of research in this field. Falkowski et al 12 and Bednarek et al 13 found monosaccharides and their derivatives were a group of effectively working processing agents for alumina suspensions with a series of advantages such as nontoxic, water soluble, inexpensive, etc. Biodegradable polymers, polyaspartic acid (PASP) and polyepoxysuccinic acid (PESA), are widely used as effective scale inhibitors even under extreme condition in water treatment 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence searching for biodegradable alternatives but still can provide low viscosity to replace traditional ceramic additives has become a focused area of research in this field. Falkowski et al 12 and Bednarek et al 13 found monosaccharides and their derivatives were a group of effectively working processing agents for alumina suspensions with a series of advantages such as nontoxic, water soluble, inexpensive, etc. Biodegradable polymers, polyaspartic acid (PASP) and polyepoxysuccinic acid (PESA), are widely used as effective scale inhibitors even under extreme condition in water treatment 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of these compounds have been elaborated by authors and described elsewhere as well as the properties of obtained ceramic parts [15][16][17]. Saccharides have many hydroxyl groups in a molecule; thereby the cross-linked polymer network can be created by forming hydrogen bonds between polymeric chains.…”
Section: Introductionmentioning
confidence: 99%
“…The sintering process generates a clean burnout on using saccharide-based derivatives compared to the conventionally used organic additives. Organic synthesis allows for modification of saccharides in different functional groups thereby opening a new range of applications in ceramic technology [89].…”
Section: Biopolymer Additivesmentioning
confidence: 99%